The importance of the exercise of strengthening in kinetic chain closed in patellar condromalacy (Research, Society and Development, 2021)
Patellar chondromalacia is the loss of patellar cartilage, and tissue stiffness may be lost or decreased. Presenting pain in the anterior region of the patella when performing activities of daily living (ADLs) and when flexing and extending the patella. Muscle strengthening exercises in closed kinetic chain offer a better result due to the functionality and the facilitation of application and promotes pain relief. The objective of this article is to verify the importance of strengthening exercises in closed kinetic chain in patellar chondromalacia, based on research found on digital platforms: Scientific Electronic Library Online (SciELO) and Google Scholar. It is concluded that muscular strengthening exercises in closed kinetic chain used in Chondromalicia Patelar, demonstrate, in their majority, effective results to reduce the pain, strengthening the whole musculature involved and providing the improved flexibility.